2018
DOI: 10.1002/pld3.65
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome assembly and annotation of johnsongrass (Sorghum halepense) rhizomes identify candidate rhizome‐specific genes

Abstract: Rhizomes facilitate the wintering and vegetative propagation of many perennial grasses. Sorghum halepense (johnsongrass) is an aggressive perennial grass that relies on a robust rhizome system to persist through winters and reproduce asexually from its rootstock nodes. This study aimed to sequence and assemble expressed transcripts within the johnsongrass rhizome. A de novo transcriptome assembly was generated from a single johnsongrass rhizome meristem tissue sample. A total of 141,176 probable protein-coding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…We found that only a small proportion of lowly expressed transcripts assembled from Bridger (11.1%), BinPacker (12.5%), SOAP denovo (6.7%), Trans-ABySS (10.3%), and Trinity (13.3%) supported by evidence of: 1) read depth > 2; 2) genome mapping rate > 50%; 3) CDS mapping rate > 60%; and 4) NR annotations (Additional file 1: Figure S3). This finding suggests the limitations of the current de novo transcriptome assemblers on the lowly expressed transcripts of tea plants, which is similar to those found in other plant species [5355]. Nevertheless, the assembly accuracy of BinPacker, Bridger and Trinity are comparable and much higher than that of SOAP denovo and Trans-ABySS regarding the construction of lowly expressed transcripts.…”
Section: Resultssupporting
confidence: 77%
“…We found that only a small proportion of lowly expressed transcripts assembled from Bridger (11.1%), BinPacker (12.5%), SOAP denovo (6.7%), Trans-ABySS (10.3%), and Trinity (13.3%) supported by evidence of: 1) read depth > 2; 2) genome mapping rate > 50%; 3) CDS mapping rate > 60%; and 4) NR annotations (Additional file 1: Figure S3). This finding suggests the limitations of the current de novo transcriptome assemblers on the lowly expressed transcripts of tea plants, which is similar to those found in other plant species [5355]. Nevertheless, the assembly accuracy of BinPacker, Bridger and Trinity are comparable and much higher than that of SOAP denovo and Trans-ABySS regarding the construction of lowly expressed transcripts.…”
Section: Resultssupporting
confidence: 77%
“…Therefore, no further research has been reported about these perennialism-related loci/genes. Recently, Ryder et al (2018) reported a set of 98 expressed contigs in Johnsongrass ( Sorghum halepense ) that are likely associated with rhizome development.…”
mentioning
confidence: 99%
“…One of the remarkable prosperity factors of Johnsongrass is selfpollination (Dweikat 2005). It blooms 46 days after emergence and produces up to 80000 seed per plant in a single season which remain viable for up to 10 years in the soil (McWhorter 1961;Ryder et al 2018). Johnsongrass has a broad seed depth germination rate ranging from 64% at 1 cm to 30% at 20 cm depth.…”
Section: Johnsongrass As Invasive Plant Speciesmentioning
confidence: 99%
“…Its bioinformatic coding sequence analysis between Thinopyrum intermedium, a rhizomatous and perennial grass, and the seasonal nonrhizomatous S. bicolor resulted in the identification of 98 candidate sequences involved in Johnsongrass rhizome development. Among these, the most expressed protein families belong to ZIM (zinc finger inflorescence meristem) family, DNA binding proteins, transcription factors and the Armadillo (ARM)repeat superfamily which have been shown to play crucial roles in hormone signaling, development by exhibiting a differential expression pattern during environmental stress responses (Ryder et al 2018). Similarly, the analysis of Johnsongrass ancestor S. propinquum promoter regions shows an enrichment of cisregulatory elements involved in abscisic acid (ABA) and gibberellic acid (GA) responses, suggesting a cross-talk between those hormones in rhizomes.…”
Section: Johnsongrass As Invasive Plant Speciesmentioning
confidence: 99%
See 1 more Smart Citation